Volume 7: Dynamic Systems and Control; Mechatronics and Intelligent Machines, Parts a and B 2011
DOI: 10.1115/imece2011-65736
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of an Elastic-Plastic Contact Model

Abstract: In many engineered structures and components, impact events frequently occur between sub-components. Numerical models are able to adequately capture the salient features of these events; however, with high fidelity finite element models, an unreasonably large number of elements are needed to accurately model just the elastic regime when arbitrary contact is considered. In order to solve real engineering problems with elastic-plastic impacts in complex or built up systems, an analytical expression is needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The model is also adaptable to macroscopic contact. Brake et al [29,30] used the Von Mises yield criterion and Brinell hardness to determine the amount of elastic-plastic deformation and plastic deformation of the asperity. Brake interpolated the elastic-plastic contact phase using Hermit polynomials to find the relationship between the contact area and the average contact pressure and deformation of the elastic-plastic phase.…”
Section: Theoretical Modeling Of Fully Elastic and Fully Plastic Defo...mentioning
confidence: 99%
“…The model is also adaptable to macroscopic contact. Brake et al [29,30] used the Von Mises yield criterion and Brinell hardness to determine the amount of elastic-plastic deformation and plastic deformation of the asperity. Brake interpolated the elastic-plastic contact phase using Hermit polynomials to find the relationship between the contact area and the average contact pressure and deformation of the elastic-plastic phase.…”
Section: Theoretical Modeling Of Fully Elastic and Fully Plastic Defo...mentioning
confidence: 99%
“…To avoid some of the main difficulties reported by other authors to obtain accurate measurements, a full-field optical technique known as 3D-DIC (Three Dimensional Digital Image Correlation) has been used. Some authors, such as preliminary studies using DIC to analyze the contact phenomenon were reported for other applications Brake et al [20] and Baca et al [21] have performed preliminary studies using the DIC technique to analyze the contact phenomena for other applications. In a contact test using conventional techniques, the indenter usually hides the area of interest and it represents a limitation in the measuring process during the experiment, as it was reported by Jamari and Schipper [22] in the experiment designed.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, although the quasi‐static elastoplastic contact models can accurately describe the relationship between the loading and displacement in the elastoplastic contact phase, they made the calculation strategy of elastoplastic contact behavior in the granular chain more complicated 16,52,54,57 . It needs to be emphasized that the elastoplastic collision in the granular chain depends on the constitutive relation of contact bodies, 46 and the convenient and straightforward calculation strategy is determined by the damping factor 26 . Therefore, this investigation not only replaces the Hertz contact stiffness of existing dashpot models in the elastoplastic phase by means of the quasi‐static elastoplastic contact model (Ma‐Liu (ML) model), but also proposes a new damping factor without initial impact velocity by solving a single‐degree‐freedom underdamped vibration equation.…”
Section: Introductionmentioning
confidence: 99%
“…43 That is mainly because the Hertz contact stiffness 44,45 overestimates the contact stiffness in the elastoplastic or plastic contact phase. Accordingly, to overcome this problem, some scholars [46][47][48][49][50][51] developed a series of quasi-static elastoplastic contact models to describe the elastoplastic contact events using the piecewise function, including the elastic, elastoplastic, and full plastic phase. Since these elastoplastic contact models depend entirely on the constitutive relation of contact bodies, they can accurately reflect the relationship between the force and displacement in the elastoplastic phase.…”
Section: Introductionmentioning
confidence: 99%